Hakikat Pemerolehan Bahasa dan Faktor-Faktor Yang Mendukung Pemerolehan Bahasa Pada Anak - Alya Nabillah; Mutiara Nurhalizah; Silvina Noviyanti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Language acquisition is a natural, multidimensional process that occurs gradually, involving the interaction between internal and external factors. Internal factors include biological readiness, such as the child's innate device for recognizing language patterns (Language Acquisition Device), cognitive development, and hereditary factors, while external factors involve social environment, family interaction, and culture. This process begins when infants learn their first language or mother tongue through direct experience and linguistic stimulation from their surroundings. Language acquisition differs from language learning because acquisition occurs unconsciously and in informal contexts, while learning is a conscious and structured process usually conducted in formal education. The first language acquisition serves as an important foundation for subsequent language abilities, and the success of this process is highly influenced by optimal support from various internal and external factors. Therefore, a deep understanding of the nature and supporting factors of language acquisition is crucial for teachers, parents, and educational practitioners to create an effective and responsive learning environment that meets children's language development needs.